1952
DOI: 10.1071/ar9520227
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus toxicity in Subterranean clover and oats grown on Muchea sand, and the modifying effects of lime and nitrate-nitrogen

Abstract: Phosphorus supplied as mono-sodium phosphate depressed the growth of subterranean clover and oats grown on Muchea sand in pot culture. In both plants the detrimental effects appeared at phosphorus levels equivalent to about 2-4 cwt. per acre superphosphate, provided both nitrogen and lime were in very short supply. Adequate nitrogen, as sodium nitrate, invariably overcame the toxic effects of phosphorus within the range of levels examined. With the clover, nodulation was usually poor, but some evidence is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1955
1955
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…Similarly, symptoms of phosphorus deficiency (3), or phosphorus toxicity (12) were in accordance with the expected phosphortus-iron ratio in each case. An examination of chlorosis due to genetical and virological causes was therefore undertaken to ascertain the trend in phosphorus-iron and calcium-potassium ratios.…”
mentioning
confidence: 81%
“…Similarly, symptoms of phosphorus deficiency (3), or phosphorus toxicity (12) were in accordance with the expected phosphortus-iron ratio in each case. An examination of chlorosis due to genetical and virological causes was therefore undertaken to ascertain the trend in phosphorus-iron and calcium-potassium ratios.…”
mentioning
confidence: 81%
“…This depressive effect of phosphate was associated with high phosphorus concentrations in the tops of all P2 and P3 plants (Table 8). In this regard Rossiter (1952) found that subterranean clover showing incipient phosphorus toxicity symptoms contained a phosphorus concentration of 1·43%.…”
Section: >mentioning
confidence: 99%
“…At the highest levels of application (1000 mg P/pot) the plants were stunted and the leaves had necrotic tips. These are symptoms of phosphorus toxicity (Rossiter, 1952). As there is no satisfactory response function to include the descending part of the response curve yields from such treatments were not used.…”
Section: Effect Of Period Of Incubation At 70° C and Of Va Mycorrhizamentioning
confidence: 99%